Estimating The Annual Cost of Smoking-Related Diseases in Indonesia - Bambang Sutrisna; Lujna Surtidewi; Anwar Jusuf; Ahmad Hudoyo; Dede Kusmana; Budhi Setianto; Endang Purwaningsih (MEDIA MEDIKA INDONESIANA, 2009)
Background: Smoking plays a role in the development of chronic diseases and causes substantial negative economic consequences. This study was carried out to estimate the annual cost of smoking-related cardio-cerebrovascular and pulmonary diseases in the population by taking into account the direct costs associated with such co-morbid conditions in Indonesia.Methods: Meta-analysis using the Mix-Programme Software of the data of patients from university medical centers who were active smokers for more than a year and more than 20-pack years or passive smokers for more than a year and diagnosed with Coronary Heart Disease, Myocardial Infarction, Stroke, COPD, Chronic bronchitis, or Lung Cancer had been conducted. Annual direct cost was taken into account using the Decision Analysis Tree Age Pro (=DATA) software; cost data related to health care expenditure were derived from secondary data sources in Jakarta. In addition, Population Attributable Risk (PAR) for each comorbid conditions was calculated based on published epidemiological data from local and international journals.Results: One-hundred and eighty-seven patients (96% male) satisfying the inclusion criteria, were analyzed, of whom confirmed diagnosis of Stroke was amongst 29% of the patients, CHD 16%, Myocardial Infarction 16%, Lung Cancer 15%, COPD 17%, and Chronic Bronchitis 7%. Mean direct annual cost was highest for Lung Cancer (Rp 51.6 million) followed by Myocardial infarction (Rp 38.5 million) and CHD (Rp 37.8 million); PAR for various co-morbid conditions (based on variations in relative risk and smoking prevalence estimates) were: Stroke 16%-26%, CHD 17%-27%, MCI 22%-33%, Lung Cancer 17%-26%, COPD 13%-21%, Chronic Bronchitis 42%-59%.Conclusions: Annual cost of smoking-related diseases in Indonesia has been estimated. The highest cost is for Lung Cancer. The highest PAR is for Chronic Bronchitis.Keywords: Smoking-related diseases, Annual cost, Indonesia. ABSTRAKEstimasi pembiayaan per tahun penyakit terkait merokok di IndonesiaLatar belakang: Merokok berkaitan dengan kejadian berbagai penyakit kronis dengan konsekuensi ekonomi berupa biaya yang sangat banyak. Penelitian ini bertujuan untuk mengestimasi biaya dampak merokok pada berbagai kondisi ko-morbid terkait penyakit jantung, otak dan paru di masyarakat Indonesia.Metode: Meta-analisis dengan Mix-Programme software pada data sekunder penderita penyakit jantung iskemik, infark miokard, stroke, COPD, bronkitis kronis atau kanker paru dari Rumah Sakit Pendidikan Jakarta dengan kriteria : perokok aktif lebih 1 tahun dan merokok lebih 20 pak/tahun atau perokok pasif lebih 1 tahun. Cost-analysis dengan Tree Age Pro (=DATA) software dilakukan untuk membandingkan pengeluaran/biaya pengobatan per tahun menurut berbagai ko-morbid. Population Attributable Risk (PAR) untuk kondisi ko-morbid merujuk perhitungan yang ada pada jurnal epidemiologi lokal maupun internasional.Hasil: Seratus delapan puluh tujuh=187 pasien (96% laki-laki) memenuhi kriteria inklusi; diantaranya 29% pasien menderita stroke, 16% penyakit jantung iskemik, 16% infark miokard, 15% kanker paru, 17% COPD, dan bronkitis kronis 7%. Rerata pengeluaran biaya per tahun tertinggi adalah kanker paru (Rp 51,6 juta), diikuti penyakit jantung iskemik (Rp 37,8 juta); dan infark miokard (Rp 38,5 juta). PAR untuk masing-masing kondisi komorbid sebagai berikut: stroke 16-26%, penyakit jantung iskemik 17-27%, infark miokard 22-33%, kanker paru 17- 26%, COPD 13-21%, dan bronkitis kronis 42-59%.Simpulan: Pengeluaran biaya per tahun tertinggi untuk penyakit terkait dampak merokok adalah kanker paru-paru dan bila PAR terbesar pada bronkitis kronis.